Trimming, Transforming Statistics, And Bootstrapping: Circumventing the Biasing Effects Of Heterescedasticity And Nonnormality. - Keselman, H. J.; Wilcox, Rand R.; Othman, Prof.Madya Abdul Rahman; Fradette, Katherine (2002)
Researchers can adopt different measures of central tendency and test statistics to examine the effect of a treatment variable across groups.